A fast track strategy toward highly functionalized dendrimers with different structural layers: an "onion peel approach"1. Issue 9 (7th March 2015) - Sharma, Rishi; Zhang, Issan; Abbassi, Leïla; Rej, Rabindra; Maysinger, Dusica; Roy, René
<x xml:space="preserve">Abstract</x> A novel strategy is described for the rapid syntheses of polyhydroxylated dendrimers in which the layer by layer building blocks are different from one another. The resulting dendrimers showed no cytotoxicity.